The theory of dominant by A.A. Ukhtomsky as a theoretical basis in the methodology of coaching - Zalavina S. E. (Coaching psychology: methodology, theory, practice, 2025)
The article is the result of theoretical analysis. The purpose of the article is to present the relationship between the theoretical and applied levels of knowledge for coaching as a methodology of practical work. At the moment, there is a gap between the applied and theoretical levels of knowledge. The objective of the article is to develop the direction of unification of levels of scientific knowledge and practically applicable methodology through theoretical analysis.
Keywords: коучинг; coaching; теоретическое обоснование коучинга; теория доминанты Ухтомского; доминанта; theoretical basis of coaching; Ukhtomsky's theory of dominant; dominant